2022
DOI: 10.5751/es-12973-270139
|View full text |Cite
|
Sign up to set email alerts
|

Result-based payments as a tool to preserve the High Nature Value of complex silvo-pastoral systems: progress toward farm-based indicators

Abstract: As shown by the Green Deal's ambition, the European Commission is progressively pushing for an environmental shift and climate action in Europe. For the Common Agricultural Policy (CAP), this involves a stronger focus on greening policy objectives. For agri-environmental schemes, this entails changes toward performance-based payments, partially replacing traditional activity-based payments. The CAP foresees greater flexibility in national programs and tailor-made solutions centered on results (i.e. environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Other processes have also highlighted the diversity of engagement moments and the importance of involving different institutions as central for success as well as for fairer and more equitable decisions (Giakoumi et al, 2018;Day et al, 2019;Scheŕéet al, 2021;Pinto-Correia et al, 2022). Yet, as Day (2017) highlighted, extensive public sessions can be less valuable than limited engagement sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Other processes have also highlighted the diversity of engagement moments and the importance of involving different institutions as central for success as well as for fairer and more equitable decisions (Giakoumi et al, 2018;Day et al, 2019;Scheŕéet al, 2021;Pinto-Correia et al, 2022). Yet, as Day (2017) highlighted, extensive public sessions can be less valuable than limited engagement sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [25,32,35,73,99] have concluded that agri-environmental payments and other guidelines for management would be much more cost-effective if they more clearly addressed the grasslands that are most valuable and that are most in need of support for maintaining appropriate grazing. Some of the evaluation studies also emphasised that a large proportion of the payments went to farms in regions with the most intensive and productive agriculture, where grazing would be economically sustainable and where farmers, to a large extent, would manage the grasslands without such payments [25,32,73].…”
Section: Cost-effectiveness Of Policy Measuresmentioning
confidence: 99%
“…The specific characteristics of HNV farmland also need to be taken into account when developing processes to monitor the success of tailor-made support measures. Pinto-Correia et al (2022) worked with farmers in southern Portugal to identify farmbased indicators that could be used by both farmers and technical staff to assess the scale of benefits being achieved by results-based measures designed to maintain the montado silvo-pastoral system. The 10 field-based visual indicators that were produced have the potential to allow farmers to understand better how effective their management practices are being and, where necessary, adapt them accordingly.…”
Section: From Understanding To Evidence-driven Solutionsmentioning
confidence: 99%